Motivation and Challenges in Learning Mandarin For Non-Chinese Descent High School Students at Methodist-6 School Medan - Shandy, Shandy; Charles, Charles; Romy, Elly; Hualangi , Cynthia (CV. Publikasi Indonesia, 2025)
This study aims to analyze the level of motivation and the difficulties faced by non-Chinese students in learning Mandarin at SMA Methodist-6 Medan. The background of this research is the increasing demand for Mandarin proficiency in Indonesia, following the growing bilateral relations between Indonesia and China and the increasing career opportunities requiring Mandarin skills. This study uses a quantitative approach with a survey method, where data is collected through questionnaires distributed to non-Chinese students. The results show that most students have high motivation to learn Mandarin, particularly instrumental motivation related to career opportunities. However, the main difficulties they face lie in writing and speaking skills, which are caused by the structural differences between Mandarin and Indonesian, as well as limited opportunities to practice outside the school environment. Additionally, there is an indication of a gap between students' high motivation and their actual ability to overcome linguistic barriers. The Pearson correlation test results show a weak and insignificant positive relationship between motivation and learning difficulties. Based on these findings, it is suggested that a more contextual and communicative learning approach should be applied to address the learning difficulties faced by students and improve their Mandarin language skills.